OP0190 UNDERSTANDING CURRENT PRESCRIPTION DRUG TREATMENT PARADIGMS FOR PATIENTS WITH OSTEOARTHRITIS IN EUROPE. (2nd June 2020) - Conaghan, P. G.; Abraham, L.; Graham-Clarke, P.; Viktrup, L.; Cappelleri, J. C.; Beck, C.; Bushmakin, A. G.; Hatchell, N.; Clayton, E.; Jackson, J.
Abstract : Background: Joint pain is the most prevalent symptom for sufferers of osteoarthritis (OA). Pharmacological management of OA is restricted by limited efficacy and considerable toxicity, with growing fears about opioid use. Objectives: To understand the current real-world prescribed drug treatment paradigm related to OA disease severity for patients in 5 EU countries; France, Germany, Italy, Spain and the UK. Methods: Data were drawn from the Adelphi OA Disease Specific Programme (2017-18), a point-in-time study of physicians and their patients. Physicians classified their patients as currently having mild, moderate or severe disease severity, and provided details on currently prescribed OA therapy and physician satisfaction with therapy, rated from very satisfied to very dissatisfied. Patients were excluded from these analyses if they suffered from back and neck OA only, and shoulder OA that had not been diagnosed by X-ray. Comparisons among disease severity groups were made using analysis of variance and chi-squared tests. Results: The study included 489 physicians (primary care physicians, rheumatologists, orthopaedists) reporting on 3596 of their OA patients: 24% mild (n=874), 53% moderate (n=1904), and 23% severe (n=818). Overall, 73% patients were prescribed at least one drug for their OA (65% of mild; 76% of moderate; 77% of severe patients [<0.001]). Paracetamol (34%) was the most commonly prescribed OA treatment. NSAIDs (31%) and opioids (27%) were also frequently prescribed treatments, and worsening severity was associated with an increase in opioid use (11% of mild; 26% of moderate, 47% of severe patients [<0.001]), but not NSAID (Table 1 ). The mean number of prescription medications increased (0.9 for mild; 1.4 for moderate; 1.6 for severe patients [<0.001]) and physician satisfaction with treatment decreased (86% for mild; 70% for moderate; 41% for severe [<0.001]) with worsening OA disease severity. Conclusion: Physicians reported decreasing satisfaction with treatment for their OA patients as disease severity increased, despite increasing use of opioids and numbers of classes of prescribed drugs. Disclosure of Interests: Philip G Conaghan Consultant of: AbbVie, BMS, Eli Lilly, EMD Serono, Flexion Therapeutics, Galapagos, GSK, Novartis, Pfizer, Speakers bureau: AbbVie, Eli Lilly, Novartis, Pfizer, Lucy Abraham Shareholder of: Pfizer, Employee of: Pfizer, Peita Graham-Clarke Shareholder of: Eli Lilly and Co, Employee of: Eli Lilly and Co, Lars Viktrup Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Joseph C Cappelleri Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Craig Beck Shareholder of: Pfizer, Employee of: Pfizer, Andrew G Bushmakin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Niall Hatchell: None declared, Emily Clayton: None declared, James Jackson: None declared